A study on the challenges faced by the Algerian students in learning English as a third language - Lebci, Zahra (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This study investigates the challenges faced by Algerian students who learn English as a third language in Algerian schools. The study aims to identify the challenges faced by Algerian secondary school students in learning English as a third language, to examine the factors that affect the challenges they face and to suggest possible solutions to overcome these challenges. The study adopted a quantitative approach and involved 357 full time secondary school students from four selected secondary schools in the Boussaada District, M'ssila State, Algeria and employed a 50-item questionnaire which probed the participants' perceptions and opinions about the challenges they face in learning English, factors that affect it and the possible solutions to the challenges. The data was analysed using descriptive and inferential statistics and the results indicate that English language learners in Algeria face several challenges, namely the lack of vocabulary in writing, insufficient amount of speaking lessons to improve speaking skills, prolonged time to recall exact pronunciation of words while giving explanation, grammar problems in writing, oral fluency and the lack of confidence while reading in class. Furthermore, the chi-square analyses conducted show that the some of the demographic elements have significance influence to these challenges, particularly gender and writing difficulties which could be overcome through writing tasks and spelling exercises. Consequently, the researcher recommends that teachers should provide learning opportunities through authentic materials and task-based activities to learn the English language. Teachers should also encourage students to read and search more materials in English in order to have a better grasp of vocabulary, focus on speaking skills by organizing scientific trips, peer-based conversation exercises inside and outside the classroom and allocate more time for speaking sessions. In addition, teachers have to provide easy grammar lessons and motivate the students.